Acute Respiratory Distress Syndrome and septic shock in pregnant woman with COVID-19 - Jesselyn Kristanti; Fransiscus OH Prasetyadi (Universitas Airlangga, 2021)
Objectives: To prove that pregnancy do not worsen the clinical course of COVID-19 compared with nonpregnant individuals as found in the first case of COVID-19 pregnant woman died in our center. Case Report: A 27-year-old female, G2P0A1 23/24 weeks without comorbidities, complaint of diarrhea and 4 days later got fever, cough, and dyspnea. She was referred to our hospital for further evaluation because of deterioration. SARS CoV-2 RT-PCR tested positive. Blood, sputum, and urine cultures tested negative. She was intubated and given LMWH. She was worsened rapidly despite being on intensive care for 3 days with last vital signs recorded: blood pressure 66/24 mmHg with vasopressors, heart rate 136 beats/minutes, temperature 41°C, oxygen saturation 62%, cardiac arrest and expired. Conclusion:COVID-19 pregnant women need proper care so that they will not fall into conditions such as ARDS and septic shock. Close monitoring on clinical and laboratory course is recommended. We suggest clinicians to be aware so as rapid deterioration and death can be avoided.